Exploring Conditions for Handling Packing and Shipping Aedes aegypti Males to Support an SIT Field Project in Brazil - Maylen Gómez; Aline T. Macedo; Michelle C. Pedrosa; Fernanda Hohana; Verenna Barros; Bianca Pires; Lucas Barbosa; Miriam Brito; Luiza Garziera; Rafael Argilés-Herrero; Jair F. Virginio; Danilo O. Carvalho (Insects, 2022)
The sterile insect technique (SIT) application, as an alternative tool for conventional mosquito control methods, has recently gained prominence. Nevertheless, some SIT components require further development, such as protocols under large-scale conditions, focusing on packing and shipping mosquitoes, and considering transporting time. Immobilization of Aedes aegypti males was tested at temperatures 4, 7, 10, and 14 °C, and each temperature was assessed for 60, 90, and 120 min. The recovery after 24 h was also studied. Chilled and control-reared males had comparable survival rates for all conditions, although 4 °C for 120 min impacted male survival. The male escape rate was affected after 60 min of exposure at 4 °C; this difference was not significant, with 24 h of recovery. First, we defined the successful immobilization at 4 °C for 60 min, thus enabling the evaluation of two transportation intervals: 6 and 24 h, with the assessment of different compaction densities of 100 and 150 mosquitoes/cm3 at 10 °C to optimize the shipment. Compaction during simulated mosquito shipments reduced survival rates significantly after 6 and 24 h. In the mating propensity and insemination experiments, the sterile males managed to inseminate 40 to 66% for all treatments in laboratory conditions. The male insemination propensity was affected only by the highest compaction condition concerning the control. The analysis of the densities (100 and 150 males/cm3) showed that a higher density combined with an extended shipment period (24 h) negatively impacted the percentage of inseminated females. The results are very helpful in developing and improving the SIT packing and shipment protocols. Further studies are required to evaluate all combined parameters’ synergetic effects that can combine irradiation to assess sexual competitiveness when sterile males are released into the field.